International communication continuity and change - Thussu, Daya Kishan (London New York Bloomsbury Academic, 2018)
"With new case studies and pedagogical features, this bestseller is compulsory reading for all media and communication studies students"-- Provided by publisher.
The historical context of international communication -- Approaches to theorizing international communication -- Creating a global communication infrastructure -- The global media market -- The global and the local in media cultures -- Contraflow in global media the globalization of China's media -- International communication in the digital age.
Includes bibliographical references and index.
Keywords: Communication, International; Mass media; Communication, International -- Case studies; Mass media -- Case studies